Two new species of Phyllophaga Harris (Coleoptera: Scarabaeidae: Melolonthinae) from Costa Rica - García-López, Alejandra; Morón, Miguel Ángel; Micó, Estefanía; Galante, Eduardo (Zootaxa, 2009)
Two new species of Phyllophaga (Phyllophaga) are described: Phyllophaga larai García-López & Morón sp. nov. and Phyllophaga copalensis García-López & Morón sp. nov. The specimens were collected in premontane rain forests located at 1000 m in altitude in the Talamanca and Guanacaste mountain ranges, Costa Rica. A distribution map, key to the two new species as well as their two nearest relatives, and illustrations of diagnostic structures are provided.